2014
DOI: 10.1016/j.foodchem.2013.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Detection of roasted and ground coffee adulteration by HPLC by amperometric and by post-column derivatization UV–Vis detection

Abstract: Coffee is one of the most consumed beverages in the world. Due to its commercial importance, the detection of impurities and foreign matters has been a constant concern in fraud verification, especially because it is difficult to percept adulterations with the naked eye in samples of roasted and ground coffee. In Brazil, the most common additions are roasted materials, such as husks, sticks, corn, wheat middling, soybean, and more recently - acai palm seeds. The performance and correlation of two chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 14 publications
0
30
0
2
Order By: Relevance
“…In another study, near‐infrared spectroscopy was successfully applied for identification and quantification of the fraudulent addition of barley in roasted and ground coffee samples (Ebrahimi‐Najafabadi et al ., ). Common methods used for the determination of coffee adulteration include high‐performance liquid chromatography (HPLC) with fluorescence detection, ultraviolet adsorption (UV), diode array detection and mass spectrometry (Ebrahimi‐Najafabadi et al ., ; Domingues et al ., ; Cai et al ., ).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In another study, near‐infrared spectroscopy was successfully applied for identification and quantification of the fraudulent addition of barley in roasted and ground coffee samples (Ebrahimi‐Najafabadi et al ., ). Common methods used for the determination of coffee adulteration include high‐performance liquid chromatography (HPLC) with fluorescence detection, ultraviolet adsorption (UV), diode array detection and mass spectrometry (Ebrahimi‐Najafabadi et al ., ; Domingues et al ., ; Cai et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Coffee is one of the most popular beverages, and its consumption has increased rapidly. However, a shortage of coffee beans has given rise to mixing pure ground coffee with coffee adulteration materials, such as spent coffee grounds, coffee berry skin, roasted barley, corn, seeds, twigs and other grains (Jham et al ., ; Oliveira et al ., ; Domingues et al ., ; Pauli et al ., ; Thorburn Burns et al ., ). Coffee was reported to be one of the top ten products having a risk of food fraud in the United States Pharmacopeia (USP) Convention (Database, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the development of reliable and specific coffee authentication methods. Near infrared (NIR) spectroscopy, mid infrared spectroscopy, gas chromatography-mass spectrometry and high performance liquid chromatography (HPLC) have been used for quality control, classification and authentication of coffee samples (Briandet et al, 1996;Domingues et al, 2014;Pizarro et al, 2007;Tavares et al, 2012). However, most of these instrumental techniques require harmful reagents and/or expensive equipment with large operational/maintenance costs (Souto et al, 2015;Souto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…HPLC and HPAEC coupled with RID , pulsed amperometric detector (PAD) and reverse pulsed amperometric detection (RPAD) have been successfully applied towards the determination of carbohydrates in different matrices as they entail direct quantification without the need for carbohydrates derivatization, are deemed relatively economical and straightforward with regard to the quantification of these compounds. In addition to the methods described in the literature, there are also application notes of equipment manufacturers and chromatographic columns for sugar analysis in biomass .…”
Section: Introductionmentioning
confidence: 99%